A new species of Microhyla (Amphibia: Anura: Microhylidae), with an extended description of Microhyla nanapollexa from Vietnam - Hoang, Chung Van; Pham, Cuong The; Nguyen, Truong Quang; Phan, Tien Quang; Ziegler, Thomas; Orlov, Nikolai; Jiang, Jianping; Do, Dang Trong (Zootaxa, 2025)
Based on morphological and molecular evidences, we describe a new species of Microhyla (Nanohyla) from Deo Ca Mountain in Vietnam. The new species differs from congeners by high genetic divergences in 12S rRNA and 16S rRNA sequences (9.31–11.28 %), surpassing known genetic distances between other recognized species of the subgenus Nanohyla. The new species revealed to be sister to M. nanapollexa from Kon Tum Province, Vietnam. Based on new findings of the latter species, including the first known males, we provide an extended diagnosis of M. nanapollexa including the first record from Kon Tum Province, Vietnam.